Production and Characterization of Two Monoclonal Antibodies Specific for Plasmopara halstedii - Bouterige, S. (American Society for Microbiology, 2000)
Sunflower downy mildew, caused by the fungus Plasmopara halstedii, is a potentially devastating disease. We produced two monoclonal antibodies (MAbs) (12C9 and 18E2) by immunizing mice with a partially purified extract of P. halstedii race 1. Both MAbs detected in enzyme-linked immunosorbent assay (ELISA) all races of P. halstedii present in France. No cross-reactions were observed with Plasmopara viticola or with other fungi commonly associated with sunflowers. Both MAbs recognized the same three fungal antigens with molecular masses of 68, 140, and 192 kDa. However, the epitopes on the fungal antigens were distinct and repetitive. Seed homogenates from infected plants were incubated in wells coated with MAb 18E2. This resulted in the trapping of P. halstedii antigens that were identified with biotinylated MAb 12C9. No reactions were seen with seed homogenates from healthy plants. Thus, our results suggest that these MAbs might be used to develop a sandwich ELISA detection system for P. halstedii in infected seeds.